Foreign language teachers organising learning during their first year of teaching young learners - Stelma, Juup; Onat-Stelma, Zeynep (Language learning journal, 2010)
This paper explores the experience of English as a foreign language (EFL) teachers moving from teaching older learners to teaching younger learners. The context of the study is the Turkish private primary school sector. In response to a 1997 educational reform, many schools in this sector introduced English as a subject in the first year of primary school (children aged seven and older). These private schools were well resourced and financially strong, but struggled to find English teachers with young learner experience. Consequently, they often hired English teachers from secondary/high schools and the adult EFL sector. The paper explores the experience of four English teachers fitting this profile during their first year of teaching English at the primary level. The analysis focuses on how the teachers organised learning in their classrooms, and how this developed over time. This was an aspect of teaching that the teachers were particularly concerned about during their first year of teaching young learners. The analysis shows how the teachers' understanding moved from a concern with controlling the behaviour of learners towards a broader conceptualisation of how one might organise learning in young learner classrooms. We believe that these teachers' development over the first year of teaching L2 English to children may offer insights for novice and more experienced teachers, of both English and other languages, faced with the challenge of teaching young learners for the first time.